PENGARUH PENGETAHUAN PRODUK, NILAI, DAN KUALITAS YANG DIPERSEPSIKAN TERHADAP KEPUASAN PELANGGAN MOBIL TOYOTA - Kussujaniatun, Sri; -, Wisnalmawati (BISMA: Jurnal Bisnis dan Manajemen, 2011)
This study indicated to examine effect product knowledge,percieved value, and percieved quality for customer satisfaction. Sample in thisstudy are the owner the Toyota number of sample count up 100 owner,technique conception of sample using. Accidental sampling. Data analyze todispose of multiple regression. The study result the product knowledge,perceived value of customer and perceived quality influential to customersatisfaction. Contribution in the knowledge to develop model concept ofmarketing, and for marketing strategy developing.